Cortical and functional responses to an early protocol of sensory re-education of the hand using audio–tactile interaction. (June 2018) - Mendes, Raquel Metzker; Rondinoni, Carlo; Fonseca, Marisa de Cássia Registro; Barbosa, Rafael Inácio; Garrido Salmón, Carlos Ernesto; Barbieri, Cláudio Henrique; Mazzer, Nilton
Introduction: Early sensory re-education techniques are important strategies associated with cortical hand area preservation. The aim of this study was to investigate early cortical responses, sensory function outcomes and disability in patients treated with an early protocol of sensory re-education of the hand using an audio-tactile interaction device with a sensor glove model. Methods: After surgical repair of median and/or ulnar nerves, participants received either early sensory re-education twice a week with the sensor glove during three months or no specific sensory training. Both groups underwent standard rehabilitation. Patients were assessed at one, three and six months after surgery on training-related cortical responses by functional magnetic resonance imaging, sensory thresholds, discriminative touch and disability using the Disabilities of the Arm, Shoulder and Hand patient-reported questionnaire. Results: At six-months, there were no statistically significant differences in sensory function between groups. During functional magnetic resonance imaging, trained patients presented complex cortical responses to auditory stimulation indicating an effective connectivity between the cortical hand map and associative areas. Conclusion: Training with the sensor glove model seems to provide some type of early cortical audio-tactile interaction in patients with sensory impairment at the hand after nerve injury. Although no differences were observed between groups related to sensory function and disability at the intermediate phase of peripheral reinnervation, this study suggests that an early sensory intervention by sensory substitution could be an option to enhance the response on cortical reorganization after nerve repair in the hand. Longer follow-up and an adequately powered trial is needed to confirm our findings.